Development and Assessment of a Paper-based Enzyme-linked Immunosorbent Assay for the Colorimetric Diagnosis of Human Brucellosis. (3rd July 2019) - Li, Xinxin; Li, Xuejing; Guo, Yuanyuan; Liu, Yushen; Mei, Shujuan; Song, Xiuling; Li, Jinhua; Grugbaye, Alvin G.; Li, Juan; Xu, Kun
Abstract: Brucellosis is one of the most common zoonotic diseases with widespread distribution. Traditional methods for diagnosis of brucellosis require long determination times with complex instruments that do not meet the needs of rapid, simple, and convenient analysis. Thus, a newly rapid and simple method for the colorimetric diagnosis of brucellosis was developed using a paper-based enzyme-linked immunosorbent assay (p-ELISA). A total of 135 serum samples were analyzed including 33 samples as healthy controls, 77 samples as the positive group with brucellosis, and 25 samples were infected with other bacteria. The major parameters were optimized for the reported protocol. To evaluate the method, receiver operating characteristic analysis and statistical analysis were carried out using these serum samples. In the established p-ELISA system, only 5 ml of serum were required to detect the antibodies of human brucellosis in suspected brucellosis patients in less than 2 hours. The receiver operating characteristic curve was plotted, and the area under the curve of receiver operating characteristic was 0.996 and shown to be a highly accurate diagnostic test. The sensitivity was determined to be 0.961, the specificity 0.983, and the cutoff value 2.260. The gray scale intensity of the human brucellosis patients group was significantly higher than for the healthy and the non-brucellosis patient groups ( p  <  0.001). This newly developed system allows the rapid and easy diagnosis of human brucellosis.